Inside Cover: Simple Engineering of Polymer–Nanoparticle Hybrid Nanocapsules (ChemNanoMat 8/2016). Issue 8 (27th July 2016) - Sciortino, Flavien; Casterou, Gérald; Eliat, Pierre‐Antoine; Troadec, Marie‐Bérengère; Gaillard, Cédric; Chevance, Soizic; Kahn, Myrtil L; Gauffre, Fabienne
Abstract : In the Communication featured on the Inside Cover, the authors use the unsuspected presence of nanodroplets (∼100 nm) in water/THF mixtures to template the formation of hybrid nanocapsules, "hybridosomes", with a shell consisting of a crosslinked network of particles and polymers. Magnetic hybridosomes prepared from iron oxide nanoparticles enhance MRI contrast, enabling the imaging of tumor areas at low dose. This universal process can be applied to various types of inorganic nanoparticles (metallic, semi‐conducting, etc.) and to mixtures, opening the way to highly multifunctional nanocapsules. More information can be found in the Communication by M. L. Kahn, F. Gauffre et al. onpage 796 in Issue 8, 2016 (DOI:10.1002/cnma.201600155 ).